Al-Mukmin Islamic Boarding School Ngruki Sukoharjo, The Misunderstood Islamic School - Taufik Nugroho; Siswanto Masruri; Ahmad Arifi (Nuansa Akademik: Jurnal Pembangunan Masyarakat, 2022)
This research started from the researchers' anxiety about the spread of information in the mass media, both print and electronic at the national and international levels about the attitudes and acts of intolerance committed by a number of alumni of the Al-Mukmin Islamic Boarding School, Ngruki, Sukoharjo. In this study, researchers will focus on the PAI curriculum and learning content of religious tolerance at PPIM Ngruki. This method of this research uses a qualitative approach. Meanwhile, the object of this research is the curriculum and implementation of Islamic religious tolerance learning. PPIM Ngruki is a Salafi Islamic boarding school. In the implementation of learning, PPIM Ngruki has two orientations, namely hard line and soft line orientation. These two learning orientations at PPIM Ngruki work since 1972-2008. The lesson contains: religious inclusiveness, equality, respecting and respecting other religions.